Biochar-loaded copper-doped nano zero-valent iron composite material as well as preparation method and application thereof

By using biochar-loaded copper-doped nano zero-valent iron composite materials in water treatment, catalyzing sulfite under light conditions, the problems of high disinfection costs and bacterial resistance in existing water treatment technologies are solved, and efficient bacterial inhibition and material recovery in water bodies are achieved.

CN119897106APending Publication Date: 2025-04-29ZHEJIANG GONGSHANG UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411933575.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing water treatment technology has problems such as high cost, low efficiency and antibiotic abuse during the disinfection process, and the high cost and oxidation of nano zero-valent iron are difficult to achieve low-cost and efficient antibacterial effects.

Method used

The composite material was prepared by liquid phase reduction method by using biochar-loaded copper-doped nano zero-valent iron composite material, and the sulfite was used to inhibit bacteria in the water under light conditions.

Benefits of technology

It has achieved efficient inhibitory effect on bacteria in water under light conditions, and due to the magnetic properties of the material, it has the prospect of recovery of catalytic materials and good large-scale application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897106A_ABST
    Figure CN119897106A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of water treatment, and particularly relates to a biochar-loaded copper-doped nano zero-valent iron composite material as well as a preparation method and application thereof. The preparation method comprises the following steps: (1) calcining biomass powder, and grinding a calcined product to obtain biochar; (2) uniformly mixing the biochar, FeSO4. 7H2O, CuSO4. 5H2O and water to obtain a mixed solution; and (3) dropwise adding a NaHB4 solution into the mixed solution, introducing nitrogen in the whole process for reaction after dropwise adding is completed, and separating, washing and freeze-drying a product after the reaction is completed to obtain the biochar-loaded copper-doped nano zero-valent iron composite material. The biochar-loaded copper-doped nano zero-valent iron composite material provided by the invention can catalyze sulfite under an illumination condition and has an efficient inhibition effect on pathogenic bacteria in a water body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of water treatment, and in particular relates to a biochar-loaded copper-doped nano zero-valent iron composite material, a preparation method and an application thereof. Background Art

[0002] Water pollution is one of the challenges to ecosystems and human health. People have always been concerned about the problem of pathogenic microorganisms in the water environment. Pathogenic microorganisms are widely present in polluted water bodies, posing a serious threat to human health and ecosystems. Due to the imperfect wastewater treatment facilities, agricultural activities and improper discharge behaviors in the urbanization process, water bodies are seriously polluted by pathogenic microorganisms, which significantly increases the risk of human illness from waterborne diseases.

[0003] Traditional disinfection processes include ultraviolet disinfection, chlorination, advanced filtration, and ozone disinfection, but all of the above disinfection processes will produce some disinfection by-products, and there are also problems such as high cost and low efficiency. Antibiotics can effectively kill bacteria, but due to the abuse of antibiotics, they can cause bacterial resistance, reduce drug efficacy, and have adverse effects on the environment and humans.

[0004] The advanced oxidation technology of producing sulfate radicals by sulfite self-oxidation has the advantage of strong oxidation ability and has good application prospects in the fields of removal of organic pollutants and disinfection of water bodies. For example, the Chinese patent with publication number CN116602317A discloses a synergistic sterilization method of a metal catalyst and a sulfite system, wherein the metal catalyst is copper ferrite, and the specific steps are: mixing copper ferrite with a sulfite solution, adding it to the water sample to be treated and stirring it evenly, and standing it for several hours; using a plate colony counting method to detect the sterilization effect of the water sample, and detecting the difference in water quality of the water sample before and after sterilization, the sterilized copper ferrite can be magnetically recovered and reused after drying. However, the amount of metal catalyst used in this technical solution is large, and the time is long, so the cost is high.

[0005] Nano zero-valent iron (nZVI) has the characteristics of small size, strong reducibility, and large specific surface area. It is one of the most widely studied nanomaterials, but it is subject to its easy aggregation and oxidation and high cost. In recent years, many studies have reported that biomass materials such as biochar and activated carbon have porosity and high specific surface area, so carbon-based materials are often used as supporting materials for nZVI. nZVI can be loaded on the surface and pores of biochar materials, which not only plays a dispersing role but also has adsorption capacity. For example, a Chinese patent with authorization publication number CN111333154B discloses a preparation method and application of micro-electrolysis materials, which includes the following steps: weigh FeSO4·7H2O and CuSO4·5H2O solid powders and dissolve them in distilled water. The mixed solution is formed, NaBH4 solid is weighed and dissolved in ultrapure water to obtain sodium borohydride solution; the sieved activated carbon is soaked in ultrapure water and dried for use; the dried activated carbon is immersed in the mixed solution; nitrogen is continuously introduced into the mixed solution and stirred; the sodium borohydride solution is added dropwise to the mixed solution at a uniform speed, and black solid particles are obtained after the reaction is completed; the prepared black solid particles are taken out, rinsed with distilled water and ethanol, and vacuum dried to obtain iron-carbon-copper ternary micro-electrolysis material, which is stored in a vacuum environment. This technical solution uses activated carbon as a carrier, which can quickly adsorb pollutants, thereby accelerating the degradation rate of pollutants by micro-electrolysis, but cannot achieve good effects on the adsorption and inhibition of pathogens.

[0006] Therefore, the design, synthesis and application of low-cost and efficient antibacterial materials are very important. Biochar-loaded copper-doped nano-zero-valent iron composite material (BC-nZVI-Cu) can catalyze sulfite to inhibit bacteria in water under light conditions. This composite material solves the problem of activated carbon being difficult to recycle, increases the active sites of the material, and has efficient photocatalytic antibacterial properties. Summary of the invention

[0007] In view of the above problems, the present invention provides a biochar-loaded copper-doped nano-zero-valent iron composite material and a preparation method and application thereof. The biochar-loaded copper-doped nano-zero-valent iron composite material provided by the present invention can catalyze sulfite under light conditions to have a high efficiency inhibitory effect on bacteria in water bodies.

[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0009] The first aspect of the present invention provides a method for preparing a biochar-loaded copper-doped nano zero-valent iron composite material, comprising the following steps:

[0010] (1) calcining biomass powder to obtain a calcined product, and grinding the calcined product to obtain biochar;

[0011] (2) mixing biochar, FeSO4·7H2O, CuSO4·5H2O and water to obtain a mixed solution;

[0012] (3) adding the NaHB4 solution dropwise to the mixed solution, introducing nitrogen gas throughout the reaction after the addition is complete, separating, washing, and freeze-drying the product after the reaction is complete, thereby obtaining a biochar-loaded copper-doped nano-zero-valent iron composite material;

[0013] The mass ratio of the biochar, FeSO4·7H2O and CuSO4·5H2O is 0.1-0.4:1-3:0.1-1; the mass ratio of Fe / Cu is 5:1.

[0014] Preferably, the biomass in step (1) is selected from at least one of corn straw, rice straw, sugar cane and walnut, and more preferably sugar cane.

[0015] Preferably, the calcination in step (1) is carried out in a tubular furnace, the heating rate of the tubular furnace is 5-15° C. / min, the calcination temperature is 600-800° C., and the calcination time is 2-6 h.

[0016] Further preferably, the heating rate of the tubular furnace is 10° C. / min, the calcination temperature is 700° C., and the calcination time is 4 h.

[0017] Further preferably, the mass ratio of the biochar, FeSO4·7H2O and CuSO4·5H2O is 0.2:1:0.16.

[0018] Preferably, the ratio of the total mass of the biochar, FeSO4·7H2O and CuSO4·5H2O to the volume of water in step (2) is 1.2-4.4 g: 100-400 mL.

[0019] Further preferably, the ratio of the total mass of the biochar, FeSO4·7H2O and CuSO4·5H2O to the volume of water in step (2) is 1.36 g:200 mL.

[0020] Preferably, before step (3), nitrogen is introduced into the mixed solution under magnetic stirring to exclude air.

[0021] Preferably, the rotation speed of the magnetic stirring is 800-1200 rpm, and the time for introducing nitrogen into the mixed solution is 0.5-1 h.

[0022] Further preferably, the rotation speed of the magnetic stirring is 1000 rpm, and the time for introducing nitrogen into the mixed solution is 0.5 h.

[0023] Preferably, the preparation method of the NaHB4 solution in step (3) is: dissolving NaHB4 in water and dissolving it completely by ultrasonication.

[0024] Preferably, the ratio of NaHB4 to water is 0.2-0.5 g: 150-250 mL.

[0025] Further preferably, the mass ratio of NaHB4 to water is 0.3g:200mL.

[0026] Preferably, the dropping speed of the NaHB4 solution in step (3) is 1-2 drops / second.

[0027] Further preferably, the dropping speed of the NaHB4 solution in step (3) is 1 drop / second, and 1 drop is about 0.05 mL.

[0028] Preferably, the reaction time in step (3) is 0.5-1.5 h, preferably 1.5 h.

[0029] Preferably, the separation in step (3) is carried out by separating the products by applying an external magnetic field.

[0030] Preferably, the washing in step (3) is performed using a mixture of water and ethanol in a volume ratio of 1:1-2, and the number of washing times is 2-4 times.

[0031] Preferably, the freeze-drying in step (3) is preceded by precooling at a temperature of -80°C for 12 hours.

[0032] Preferably, the freeze-drying temperature in step (3) is -52°C, and the freeze-drying time is 10-12 hours.

[0033] The second aspect of the present invention provides a biochar-loaded copper-doped nano-zero-valent iron composite material obtained by the preparation method of the above-mentioned biochar-loaded copper-doped nano-zero-valent iron composite material.

[0034] The third aspect of the present invention provides the use of the above-mentioned biochar-loaded copper-doped nano zero-valent iron composite material in the preparation of a product for inhibiting the growth of pathogens in water bodies.

[0035] The fourth aspect of the present invention provides a method for inhibiting the growth of pathogenic bacteria in water, comprising the following steps: dispersing the above-mentioned biochar-loaded copper-doped nano zero-valent iron composite material in water to obtain a mixed solution A; dissolving sulfite in water to obtain a mixed solution B, adding the mixed solution A and the mixed solution B to the water sample to be treated, stirring evenly, and then treating with light.

[0036] Preferably, the pathogenic bacteria include but are not limited to Escherichia coli, Staphylococcus aureus, Mycobacterium tuberculosis, Shigella dysenteriae, Salmonella typhi, and Cholera bacilli, preferably Staphylococcus aureus and Escherichia coli.

[0037] Preferably, the concentration of the mixed solution A is 100-1000 mg / L; the concentration of the mixed solution B is 50-1250 mg / L.

[0038] Further preferably, the concentration of the mixed solution A is 100-700 mg / L, preferably 100-200 mg / L or 600-700 mg / L.

[0039] Further preferably, the concentration of the mixed solution B is 75 mg / L.

[0040] Preferably, the volume ratio of the mixed solution A, the mixed solution B and the water sample to be treated is 0.15-0.25:0.15-0.25:5-15.

[0041] Further preferably, the volume ratio of the mixed solution A, the mixed solution B and the water sample to be treated is 0.2:0.2:5-15.

[0042] Preferably, the sulfite is sodium sulfite.

[0043] Preferably, the light treatment uses xenon lamp light, and the light power is 500-900mW, preferably 800mW.

[0044] Preferably, the light treatment time is 5-60 min, more preferably 5-20 min, most preferably 20 min.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] 1. The present invention adopts self-made biochar and liquid phase reduction method, and unexpectedly finds that the biochar-loaded copper-doped nano zero-valent iron composite material obtained by controlling the mass ratio of biochar, FeSO4·7H2O and CuSO4·5H2O to 0.1-0.4:1-3:0.1-1 has a larger specific surface area, more pores, and oxygen-containing functional groups, has a strong adsorption capacity for pollutants, and takes into account biological carbon fixation and emission reduction.

[0047] 2. The biochar-loaded copper-doped nano-zero-valent iron composite material provided by the present invention can catalyze sulfite under light conditions and has a high inhibitory effect on bacteria in water bodies. At the same time, due to the presence of nano-zero-valent iron magnetic metal elements in the composite material, the catalytic material can be recovered, and it has good prospects for large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is a scanning electron microscope (SEM) image of the biochar-loaded copper-doped nano-zero-valent iron composite material of Example 1;

[0049] Figure 2 This is a scanning electron microscope-energy spectrum (SEM-EDS) image of the biochar-loaded copper-doped nano zero-valent iron composite material of Example 1;

[0050] Figure 3 This is a mass percentage distribution diagram of the biochar-loaded copper-doped nano zero-valent iron composite material of Example 1;

[0051] Figure 4 This is the XRD diagram of the biochar-loaded copper-doped nano-zero-valent iron composite material of Example 1. In the figure, PDF#99-000-0814 is the XRD standard card of Cu, and PDF#99-000-1743 is the XRD standard card of Fe;

[0052] Figure 5 The antibacterial effect diagram of the biochar of Example 1, the biochar-loaded copper-doped nano zero-valent iron composite material of Example 1, Comparative Examples 1-2, and Comparative Example 5, and the biochar-loaded nano zero-valent iron of Comparative Example 3 and the copper-doped nano zero-valent iron of Comparative Example 4 on Escherichia coli under light conditions. In the figure, the mark ** (p<0.01) indicates that the difference between the two groups of data is very significant, and the mark *** (p<0.001) indicates that the difference between the two groups of data is extremely significant;

[0053] Figure 6 The antibacterial effect diagram of the biochar of Example 1, the biochar-loaded copper-doped nano-zero-valent iron composite material of Example 1, Comparative Examples 1-2, and Comparative Example 5, and the biochar-loaded nano-zero-valent iron of Comparative Example 3 and the copper-doped nano-zero-valent iron of Comparative Example 4 on Staphylococcus aureus under light conditions. In the figure, the mark ** (p<0.01) indicates that the difference between the two groups of data is very significant, and the mark *** (p<0.001) indicates that the difference between the two groups of data is extremely significant;

[0054] Figure 7 This is a diagram showing the antibacterial effect of the biochar-loaded copper-doped nano-zero-valent iron composite material under different illumination times of Example 1;

[0055] Figure 8 This is a diagram of the antibacterial effect of the biochar-loaded copper-doped nano-zero-valent iron composite material of Example 1 at different concentrations and under light and dark conditions. In the figure, the mark ** (p<0.01) indicates that the difference between the two groups of data is very significant, and the mark *** (p<0.001) indicates that the difference between the two groups of data is extremely significant. DETAILED DESCRIPTION

[0056] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0057] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0058] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0059] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0060] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0061] In the following examples and comparative examples, unless otherwise specified, all raw materials used were commercially available or prepared by conventional methods in the art.

[0062] Example 1

[0063] A method for preparing a biochar-loaded copper-doped nano zero-valent iron composite material comprises the following steps:

[0064] (1) The sugarcane powder was placed in a ceramic crucible, placed in a tube furnace, and heated to 700°C at a heating rate of 10°C / min, kept at this temperature for 4 h, and taken out after cooling down to obtain fluffy "mushroom-shaped" biochar. The biochar was ground in an agate mortar to obtain biochar, recorded as BC;

[0065] (2) 0.2 g of biochar, 1 g of FeSO4·7H2O, 0.16 g of CuSO4·5H2O and 200 mL of water were mixed to obtain a mixed solution; a 500 mL three-necked flask was placed on a magnetic stirrer at a magnetic stirring speed of 1000 rpm, the mixed solution was added to the three-necked flask, high-purity nitrogen was introduced, and the mixture was fully reacted for 30 min to remove the air in the flask;

[0066] (3) 0.3 g NaHB4 was dissolved in 200 mL water and ultrasonicated for 5 min to completely dissolve it to obtain NaHB4 solution; the NaHB4 solution was placed in a constant pressure funnel and dripped into the mixed solution at a rate of 1 drop / second, with 1 drop of about 0.05 mL. After the dripping was complete, high-purity nitrogen was introduced throughout the reaction for 1.5 h. After the reaction was completed, the product was separated by an external magnetic field, washed three times with anhydrous ethanol and deionized water (V:V=1:1), placed in a -80°C refrigerator for precooling for 12 h, and then placed in a freeze dryer for freeze drying at -52°C for 12 h to obtain a biochar-loaded copper-doped nano-zero-valent iron composite material, recorded as BC-nZVI-Cu (5:1).

[0067] Comparative Example 1

[0068] The difference from Example 1 is that in step (2), 0.2 g of biochar, 1 g of FeSO4·7H2O, 0.8 g of CuSO4·5H2O and 200 mL of water are evenly mixed to obtain a mixed solution; the rest are the same, recorded as BC-nZVI-Cu (1:1).

[0069] Comparative Example 2

[0070] The difference from Example 1 is that in step (2), 0.2 g of biochar, 1 g of FeSO4·7H2O, 0.11 g of CuSO4·5H2O and 200 mL of water are evenly mixed to obtain a mixed solution; the rest are the same, recorded as BC-nZVI-Cu (7:1).

[0071] Comparative Example 3

[0072] The difference from Example 1 is that in step (2), only 0.2 g of biochar and 1 g of FeSO4·7H2O were weighed, and no CuSO4·5H2O was added to obtain biochar loaded with nano zero-valent iron, denoted as BC-nZVI; the rest are the same.

[0073] Comparative Example 4

[0074] The difference from Example 1 is that in step (2), only 1 g of FeSO4·7H2O and 0.16 g of CuSO4·5H2O were weighed, and no biochar was added to obtain copper-doped nano zero-valent iron, which was recorded as nZVI-Cu; the rest are the same.

[0075] Comparative Example 5

[0076] The solution of Example 1 recorded in the Chinese patent with the authorization publication number CN111333154B is adopted, that is:

[0077] A method for preparing a biochar-loaded copper-doped nano zero-valent iron composite material comprises the following steps:

[0078] Step 1: According to the molar ratio of CuSO4·5H2O to FeSO4·7H2O of 1:9, 0.993g FeSO4·7H2O and 0.099g CuSO4·5H2O solid powders were weighed and dissolved in distilled water to form a mixed solution; according to the molar ratio of FeSO4·7H2O to NaBH4 of 1:6, 0.811g NaBH4 solid was weighed and dissolved in ultrapure water to prepare a sodium borohydride solution.

[0079] Step 2: Pass the activated carbon through a 100-mesh sieve, soak it in ultrapure water for 24 hours, and then dry it for later use.

[0080] Step 3: According to the mass ratio of total iron content in the mixed solution to activated carbon of 1:5, 1 g of dried activated carbon was immersed in the mixed solution for 10 minutes.

[0081] Step 4: Nitrogen was continuously introduced into the mixed solution and magnetic stirring was performed at a stirring speed of 1000 rpm.

[0082] Step 5: sodium borohydride solution was added dropwise to the mixed solution at a rate of 5 mL / min, and black solid particles were obtained after the reaction was completed.

[0083] Step 6: Take out the prepared black solid particles, rinse them with distilled water and ethanol, and then vacuum dry them at 40° C. for 6 h to obtain AC-nZVI-Cu.

[0084] Application Example 1

[0085] (1) Weigh 6 mg of the sugarcane biochar of Example 1, the biochar-loaded copper-doped nano-zero-valent iron composite material of Example 1, Comparative Examples 1-2, and Comparative Example 5, the biochar-loaded nano-zero-valent iron of Comparative Example 3, and the copper-doped nano-zero-valent iron of Comparative Example 4, and add them into 10 mL of deionized water to prepare a mixed solution A with a concentration of 600 mg / L for later use; weigh 7.5 mg of sodium sulfite and place it in 100 mL of deionized water to prepare a mixed solution B with a concentration of 75 mg / L for later use;

[0086] (2) Prepare 0.85% wt / vol saline: weigh 4.25 g of sodium chloride granules and add to 500 mL of deionized water;

[0087] Prepare solid LB medium: add 5g sodium chloride, 10g peptone, and 5g yeast powder to 1L deionized water in proportion, use an ultrasonic cleaner to sonicate for 10 minutes, and after the solution is dissolved, put it into a conical flask with 15-17.5mg agar powder;

[0088] Prepare liquid LB medium: add 5g sodium chloride, 10g peptone, and 5g yeast powder to 1L deionized water in proportion, use an ultrasonic cleaner to sonicate for 10 minutes, and after the solution is dissolved, dispense it into glass test tubes, 4mL per test tube, sterilize it in a high pressure sterilizer at 121℃ for 15 minutes, and cool it for later use;

[0089] (3) Take the E. coli stored at -80°C and streak it on the solid LB medium plate obtained in step (2), invert it and activate it at 37°C overnight; then pick a single clone in a test tube containing 4 mL of liquid LB medium, culture it at 37°C and 250 rpm overnight on a shaker, take 1 mL of activated bacteria and centrifuge it at a temperature of 4°C, a speed of 7000 rpm, and a centrifugation time of 3 min to remove the medium, and then dilute the bacteria with sterile saline to dilute the bacterial solution to about 10 7 CFU / mL, obtained the E. coli test bacteria;

[0090] (4) Using a beaker as a reaction container and 10 mL of sterile physiological saline as a reaction solution, the E. coli test bacteria were placed on a magnetic stirrer at a speed of 100 rpm, and 200 μL of mixed solution A and mixed solution B were added respectively. The mixture was treated under light, and the light intensity of the xenon lamp system was 800 mW. After 40 minutes, samples were taken and the bacteria were counted using the plate count method. The results are as follows: Figure 5 shown.

[0091] Application Example 2

[0092] (1): Same as Application Example 1;

[0093] (2): Same as Application Example 1;

[0094] (3) Take the Staphylococcus aureus stored at -80°C and streak it on the solid LB medium plate obtained in step (2), invert it and activate it at 37°C overnight; then pick a single clone and put it in a test tube containing 4 mL of liquid LB medium, culture it overnight on a shaker at 37°C and 250 rpm, take 1 mL of activated bacteria and centrifuge it at a temperature of 4°C, a speed of 7000 rpm, and a centrifugation time of 3 min to remove the medium, and then dilute the bacteria with sterile saline to dilute the bacterial solution to about 10 7 CFU / mL, obtained Staphylococcus aureus test bacteria;

[0095] (4) Using a beaker as a reaction container and 10 mL of sterile physiological saline as a reaction solution, Staphylococcus aureus test bacteria were placed on a magnetic stirrer at a speed of 100 rpm. 200 μL of mixed solution A and 200 μL of mixed solution B were added respectively. The mixture was treated under light. The light intensity of the xenon lamp system was 800 mW. After 40 minutes, samples were taken and the bacteria were counted using the plate count method. The results are as follows: Figure 6 shown.

[0096] Depend on Figure 5 , Figure 6 It can be seen that BC-nZVI-Cu (5:1) prepared in Example 1 can better catalyze sulfite to have the best inhibitory effect on Escherichia coli and Staphylococcus aureus under light conditions.

[0097] In conclusion, BC-nZVI-Cu(5:1) has good antibacterial properties in catalyzing sulfite under light conditions, providing a new and effective material and method for environmental microbial contamination.

[0098] Application Example 3

[0099] The difference from Application Example 1 is that in step (1), only 6 mg of the biochar-loaded copper-doped nano-zero-valent iron composite material of Example 1 is weighed and added to 100 mL of deionized water to prepare a mixed solution A with a concentration of 600 mg / L; in step (4), samples are taken at 5 min, 10 min, 20 min, 30 min, and 60 min; the rest are the same. The results are as follows Figure 7 shown.

[0100] Depend on Figure 7 It can be seen that in the Control group without any treatment and the group only adding sodium sulfite solution S(Ⅳ), the number of surviving bacteria during the 60-minute illumination period was higher than that in the group treated with the composite system of sodium sulfite solution + biochar loaded with copper-doped nano zero-valent iron composite material (S(Ⅳ) + BC-nZVI-Cu) of Example 1; as time went by, the number of Escherichia coli in the composite system treatment group gradually decreased, and all the Escherichia coli in the system died in about 20 minutes.

[0101] Application Example 4

[0102] The difference from Application Example 1 is that: step (1) weighs 1 mg, 2 mg, 3 mg, 4 mg, 5 mg, and 6 mg of the biochar-loaded copper-doped nano-zero-valent iron composite material of Example 1, respectively, and places it in 10 mL of deionized water for ultrasonication for 10 min to obtain mixed solutions A of different concentrations for use; step (4) conducts the experiment under light or dark conditions, and samples are taken after 30 min; the rest are the same, and the results are as follows Figure 8 shown.

[0103] Depend on Figure 8 It can be seen that when the sodium sulfite solution is 75 mg / L, with the increase of the concentration of the biochar-loaded copper-doped nano zero-valent iron composite material in Example 1, the antibacterial effect has a tendency to gradually increase, and the number of colonies in each group is lower than that of the Control group without any treatment; after 30 minutes, it was obviously found that light conditions are beneficial to the inhibition of Escherichia coli. When the concentration of the biochar-loaded copper-doped nano zero-valent iron composite material in Example 1 is 100, 200, 600, and 700 mg / L, the antibacterial effects of light and darkness are significantly different.

[0104] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a biochar-loaded copper-doped nano zero-valent iron composite material, characterized in that: The following steps are involved: (1) calcining biomass powder to obtain a calcined product, and grinding the calcined product to obtain biochar; (2) mixing biochar, FeSO4·7H2O, CuSO4·5H2O and water to obtain a mixed solution; (3) adding the NaHB4 solution dropwise to the mixed solution, introducing nitrogen gas throughout the reaction after the addition is complete, separating, washing, and freeze-drying the product after the reaction is complete, thereby obtaining a biochar-loaded copper-doped nano-zero-valent iron composite material; The mass ratio of the biochar, FeSO4·7H2O and CuSO4·5H2O is 0.1-0.4:1-3:0.1-1; the mass ratio of Fe / Cu is 5:

1.

2. The preparation method according to claim 1, characterized in that: The biomass described in step (1) is selected from at least one of corn straw, rice straw, sugarcane and walnut; the calcination is carried out in a tubular furnace, the heating rate of the tubular furnace is 5-15°C / min, the calcination temperature is 600-800°C, and the calcination time is 2-6h.

3. The preparation method according to claim 2, characterized in that: The heating rate of the tubular furnace is 10°C / min, the calcination temperature is 700°C, and the calcination time is 4h.

4. The preparation method according to claim 3, characterized in that: The mass ratio of the biochar, FeSO4·7H2O and CuSO4·5H2O is 0.2:1:0.

16.

5. The preparation method according to claim 4, characterized in that: The reaction time in step (3) is 0.5-1.5h.

6. The biochar-loaded copper-doped nano zero-valent iron composite material obtained by the preparation method according to any one of claims 1 to 5.

7. Use of the biochar-loaded copper-doped nano zero-valent iron composite material obtained by the preparation method according to any one of claims 1 to 5 in the preparation of products for inhibiting the growth of pathogens in water bodies.

8. A method for inhibiting the growth of pathogenic bacteria in water, characterized in that: The method comprises the following steps: dispersing the biochar-loaded copper-doped nano zero-valent iron composite material obtained by the preparation method according to any one of claims 1 to 5 in water to obtain a mixed solution A; Dissolve sulfite in water to obtain mixed solution B, add mixed solution A and mixed solution B into the water sample to be treated, stir evenly, and then treat with light.

9. The method according to claim 8, characterized in that The concentration of the mixed solution A is 100-1000 mg / L; the concentration of the mixed solution B is 50-1250 mg / L.

10. The method according to claim 8, characterized in that The volume ratio of the mixed solution A, the mixed solution B and the water sample to be treated is 0.15-0.25:0.15-0.25:5-15.

Citation Information

Patent Citations

  • A method for preparing and applying micro-electrolysis materials

    CN111333154B

  • Cooperative sterilization method based on metal catalyst and sulfite system

    CN116602317A